Analisis Pengelolaan Dana Desa Berdasarkan Peraturan Menteri Dalam Negeri Republik Indonesia Nomor 20 Tahun 2018 - Nilam Noer Faizah; Cholis Hidayati (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to determine the management of village funds in Wading Village, Sidayu District, Gresik Regency when viewed from the Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 20 of 2018. This research is qualitative research with a focus on using descriptive analysis. Data collection methods include observation, interviews and documentation with related parties regarding the implementation of village fund management which includes planning, implementation, administration, reporting and accountability. The results of the research show that the financial management planning process in Wadeng Village is in accordance with Minister of Home Affairs Regulation Number 20 of 2018. There is only one provision that is not in accordance, namely in Article 32 paragraph (3) where the RAPBDes is agreed together with the BPD, namely in October of the current year , while Wadeng Village is still experiencing delays in obtaining a collective agreement, namely in December due to several activities that hinder the plan. The implementation process, administration, reporting and accountability for financial management in Wadeng Village is in accordance with Minister of Home Affairs Regulation Number 20 of 2018. Keywords: Permendagri Number 20 of 2018, Village Fund Management, Village Government.